Receptors that bind to PEDF and their therapeutic roles in retinal diseases - Xu, Manhong; Chen, Xin; Yu, Zihao; Li, Xiaorong (Frontiers in Endocrinology, 2023)
Retinal neovascular, neurodegenerative, and inflammatory diseases represented by diabetic retinopathy are the main types of blinding eye disorders that continually cause the increased burden worldwide. Pigment epithelium-derived factor (PEDF) is an endogenous factor with multiple effects including neurotrophic activity, anti-angiogenesis, anti-tumorigenesis, and anti-inflammatory activity. PEDF activity depends on the interaction with the proteins on the cell surface. At present, seven independent receptors, including adipose triglyceride lipase, laminin receptor, lipoprotein receptor-related protein, plexin domain-containing 1, plexin domain-containing 2, F1-ATP synthase, and vascular endothelial growth factor receptor 2, have been demonstrated and confirmed to be high affinity receptors for PEDF. Understanding the interactions between PEDF and PEDF receptors, their roles in normal cellular metabolism and the response the initiate in disease will be accommodating for elucidating the ways in which inflammation, angiogenesis, and neurodegeneration exacerbate disease pathology. In this review, we firstly introduce PEDF receptors comprehensively, focusing particularly on their expression pattern, ligands, related diseases, and signal transduction pathways, respectively. We also discuss the interactive ways of PEDF and receptors to expand the prospective understanding of PEDF receptors in the diagnosis and treatment of retinal diseases.